Using Carbon Paste Electrode Modified with Ion Imprinted Polymer and MWCNT for Electrochemical Quantification of Methylmercury in Natural Water Samples - Mesa, Ruddy; Khan, Sabir [UNESP]; Sotomayor, Maria D. P. T. [UNESP]; Picasso, Gino (MDPI, 2022)
Methylmercury (MeHg) is one of the most toxic organic mercury compounds found in the environment. The continuous exposure of human beings to this highly toxic compound may damage their nervous system. The present work reports the development and application of a novel electrochemical sensing technique for the quantification of MeHg using a modified carbon paste electrode with multi-walled carbon nanotubes (MWCNTs) combined with ion imprinted polymer, which is highly selective toward MeHg (CPE/MWCNTs/IIP-MeHg) detection. The ion imprinted polymer was synthesized using 2-mercaptobenzothiazole (MBT), acrylic acid (AA) and MeHg employed as ligand, functional monomer and template ion, respectively, and the synthesized material was characterized by Raman spectroscopy and SEM-EDX. Both the proposed and control sensors were characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The electrochemical measurements were carried out using differential pulse stripping voltammetry (DPSV), and a well-defined anodic peak observed at about +0.138 V (vs. Ag/AgCl) was recorded for MeHg. The application of the CPE/MWCNTs/IIP-MeHg sensor (which increased the charge transfer on the electrode surface) under the DPSV-based electrochemical method (which enhanced the signal intensity) made the detection technique highly sensitive and selective for the quantification of methylmercury. Under optimum experimental conditions, the proposed sensor exhibited a linear response range of 560–610 µg L−1 and a detection limit of 0.538 µg L−1, with acceptable relative error values ≤1% when applied for the detection of MeHg in real water samples.
Keywords: electrochemical sensor; IIPs; methylmercury quantification